La ricezione della linguistica strutturale in Italia (Atti del Sodalizio Glottologico Milanese, 2023)
The reception of structuralism by Italian linguists can be divided into three periods. In the first of them (roughly, from the 1930s to the end of the 1950s), structural linguistics, while by no means ignored, is essentially rejected (with some exceptions, such as G. Contini or L. Heilmann). The second period roughly coincides with the 1960s, when structural linguistics reaches the height of its success, thanks, primarily, to the work of scholars such as T. De Mauro, G. Lepschy and L. Rosiello. The success of structural linguistics in Italy began to decline from the 1970s onwards: various linguists turned to other conceptual frameworks, such as generative grammar. Some possible reasons for this decline are investigated here.
Keywords: History of Linguistics; Italian Linguists; Historicism; Structuralism; Generative Linguistics